De højkirkeliges forhistorie - Kofod-Svendsen, Flemming (Kirkehistoriske Samlinger, 2007)
The previous history of the High Church The word High Church with different content In Denmark the word High Church has been used with rather different contents. 1. High Church as a characterization of the Lutheran orthodoxy. 2. High Church in the 19th century as a characterization of bishops and pastors who in some ways were forerunners of Kirkeligt Centrum (founded 1899). The new High Church The new High Church in the 20th century refused to have the same theological position as the High Church in the 19th century. They are of the opinion that they are a part of an international movement which emerged in the first decades ofthe 19th century in several protestant churches. The church, the liturgy, the sacraments and the ministry with apostolic succession were the key issues. In England Henry Newman with the Tractsfor the Times elaborated the High Church key issues. When Newman converted to the Roman Catholic Church Edward Pusey became leader of the anglo-catholic movement also called the Oxford Movement. In 1893 Father Herbert Kelly founded The Society ofthe Sacred Mission with The Theological College at Kelham. In Germany theologians as Theodor Kliefoth and W. Lohe worked out the High Church theology in opposition to the liberal theology. The High Church in Sweden collected inspiration from England and Germany. The new High Church in Denmark claims that Grundtvig is the first genuine Danish High Church character. They have some good arguments but Grundtvig was not High Church in his evaluation of the service. The new High Church in Denmark began in the 1920th with the magazines Kirke og Folk and Kirken. They introduced the new liturgical movement which got inspiration from the Roman Catholic Church particularly the monasteries in Beuron and Maria Laach in Germany and Solesmes in France. In the following years we find scattered High Church groups: 1. Theologisk Oratorium (1927) sprouted up under inspiration from Kelham. Theologisk Oratorium is not a specific High Church organization but it gave inspiration to the new High Church. 2. Some new High Church persons had relation to Thomas Laub. 3. Hans Justesen established the Student Movement Studenternes kirkelige Frivilligkreds I Studenterkredsen Ung Kirke (1935), Collegium Trinitatis (1943) and Kirkeligt Konvent af 1946 with inspiration from Swedish High Church. Justesen emphasized the reality of the sacraments and the authority of the ministry. 4. Stille Dage inspired by the English Retreats began in Helsingør in 1931 using the Hours (Mattins, Vespers, Compline etc.). 5. The three organizations Sankt Ansgars Broderskab (founded in 1932), De økumeniske Mindresøstre (founded in 1946) and Sankt Ansgars Søstersamfund (constituted in 1950). They all formed an order for the spiritual life focusing on auricular confession and the Hours. 6. Sankt Ansgar Ordenen was founded 1946 with the purpose of calling busy men who had drifted away from the church back to the church-fellowship.7. Convent in Kollund created an evangelical Lutheran Convent, a sister organization with promises, habit of an order, the Hours and worship. 8. Samfundet Pro Ecclesia was founded in 1937 with the purpose of enhancing people’s knowledge and use of Christian liturgical art in church and home. 9. Vesperringen af 1949 tried to extend people’s knowledge and use of the Hours with Gregorian chant and Bible reading. The new High Church movement takes shape 1. Vicar Børge Barsøe, Virring (1938-79) developed a marked High Church thinking with a liturgy including Roman Catholic elements in the Sunday Service. He got the inspiration from the Roman Catholic Church and the High Church in England and Sweden particularly vicar Rosendal in Osby. People in his congregation accused him of being a Roman Catholic. A trial from 1952 with a dean and a judge of a lower court made an inquiry and concluded that Barsøe could continue in his office. But he had to change some things in conduct of his office. The High Church took the decision as a victory. In the following years Barsøe was unofficially the leader of the High Church movement, and every year he was host for a clerical conference. 2. The 12th of October 1956 vicar Poul Ulsdall gave a lecture to a clerical conference. The topic of his speech was: “From Lindhardt to Barsøe«. The lecture was published in Præsteforeningens Blad and caused some public debate. 3. The 2nd of September 1957 four vicars founded Christi Legems Broderskab (Fraternitas Corporis Christi). They adopted an order for their brotherhood with a characteristic Roman Catholic tendency. 4. Whitsun 1958 the first issue of a new magazine Re-Formatio appeared with the subtitle: Communication about ecclesiastical renewal in Denmark. The High Church was now an established ecclesiastical movement in the established church in Denmark.